2016
DOI: 10.1111/aji.12516
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor‐1 4G/5G Polymorphism is Associated with Reproductive Failure: Metabolic, Hormonal, and Immune Profiles

Abstract: PAI-1 4G/5G polymorphism plays a major role in the pathogenesis of RPL and RIF by altering metabolic and immunological profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…This result agrees with another study which has detected an increased incidence of the 4G allele and/or 4G/4G genotype among the patients with RPL [10]. Moreover, the prevalence of homozygous PAI-1 4G/4G polymorphism was demonstrated to be higher in patients with RIF and RPL [19]. It was also reported that low molecular weight heparin and metformin have been demonstrated to improve implantation process and ameliorate pregnancy complications in patients with 4G/4G genotype because of the hypofibrinolytic impact of overexpressed PAI-1 on implantation [20].…”
Section: Discussionsupporting
confidence: 92%
“…This result agrees with another study which has detected an increased incidence of the 4G allele and/or 4G/4G genotype among the patients with RPL [10]. Moreover, the prevalence of homozygous PAI-1 4G/4G polymorphism was demonstrated to be higher in patients with RIF and RPL [19]. It was also reported that low molecular weight heparin and metformin have been demonstrated to improve implantation process and ameliorate pregnancy complications in patients with 4G/4G genotype because of the hypofibrinolytic impact of overexpressed PAI-1 on implantation [20].…”
Section: Discussionsupporting
confidence: 92%
“…PAI-1 expression by decidual cells has been reported to play a decisive role in regulating proteolysis, migration of endothelial cells, and remodeling of maternal tissue during human implantation [27,28,30,31]. Any disturbance in PAI-1 levels may lead to various pregnancy complications, including recurrent pregnancy losses, preeclampsia, intrauterine growth restriction, endometriosis and polycystic ovary syndrome, and unrestricted trophoblastic invasion leading to placenta accrete [30][31][32][33]. Since rhythmicity in PAI-1 expression and secretion levels must exist at varied intervals to maintain pregnancy till term, in the context of possible hMESCs secretome application, both overexpression and knockout of PAI-1 may have sense, depending on nature and stage of the disease supposed to be cured.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies have shown the importance of genes that control the fibrinolysis process (degradation of fibrin by plasmin enzyme, leading to the dilution of thrombus), such as the plasminogen activator inhibitor-1 (PAI-1) gene that impedes fibrinolysis through inhibition of the enzymes involved in the conversion of plasminogen to plasmin. Several studies have reported an association between the PAI-1 rs1799889 (4G/5G) polymorphism and iRPL, because this polymorphism can generate high levels of its protein and increase resistance to fibrinolysis [45,50,[52][53][54]55]. Salazar et al showed that this genetic variant can alter the metabolic and immunological profiles of patients with iRPL [54].…”
Section: Genetic Variants That Affect Hemostasis and Thrombophilia Sumentioning
confidence: 99%
“…Several studies have reported an association between the PAI-1 rs1799889 (4G/5G) polymorphism and iRPL, because this polymorphism can generate high levels of its protein and increase resistance to fibrinolysis [45,50,[52][53][54]55]. Salazar et al showed that this genetic variant can alter the metabolic and immunological profiles of patients with iRPL [54]. Although a meta-analysis of this polymorphism conducted by Su et al failed to find an association with iRPL, the authors suggested that it was due to the high heterogeneity of the studies and emphasized the importance of PAI-1 in the fibrinolysis process, not only in the removal of thrombus but also in the processes of tissue remodeling during embryo implantation and placentation [57].…”
Section: Genetic Variants That Affect Hemostasis and Thrombophilia Sumentioning
confidence: 99%